Unique family process: From formality to modernity - Pariasca Martínez, Jorge (2022)
The unique process has been strengthened with the adoption of two directives within the Judiciary, which promote virtuality, concentration of procedural acts and orality. In this way, this branch of the State evidences its commitment to the progress of family procedural law and the expeditious settlement of cases in favor of children and adolescents. The author of this article analyzes directives from the jurisdictional scope, developing contributions for the correct use by the judicial user.